Utilization of Corn Husk and Corn Cob Waste (Zea mays L.) on the Productivity of White Oyster Mushrooms (Pleurotus ostreatus) with Rice Washing Water Nutrients: Pemanfaatan Limbah Klobot dan Tongkol Jagung (Zea mays L.) terhadap Produktivitas Jamur Tiram Putih (Pleurotus ostreatus) dengan Nutrisi Air Cucian Beras - Siti Ainuna Rohma; Dwi Haryanta; Marmi (Journal of Applied Plant Technology, 2026)
The cultivation of white oyster mushrooms (Pleurotus ostreatus) requires a growing medium that contains nutrients to support their growth and productivity. The use of agricultural waste in the form of corn cobs and husks with the addition of rice water nutrients has the potential to be an environmentally friendly and economically valuable alternative growing medium. This study aims to determine the effect and effectiveness of using corn cobs and corn cobs with rice washing water nutrients as a growing medium on the growth and productivity of white oyster mushrooms. This study used a quantitative method with an experimental research design through a completely randomized design (CRD) consisting of 6 treatments and 5 replicates. Data analysis used a one-way ANOVA test, followed by a Least Significant Difference (LSD) test at a 5% level. The results showed that the use of corn cob and cob planting media with rice washing water nutrients had a significant effect on white oyster mushroom cultivation. The 100% corn cob treatment (K2) was effective for mycelium growth and cap width, while the 100% corn husk treatment (K1) was effective in increasing the number of fruit bodies and stem length. The combination of 50% corn husk and 50% corn cob (K5) was the most effective treatment, producing the highest productivity based on fresh harvest weight.